Implementasi Nilai -Nilai Pancasila dalam kegiatan PKK di Desa Sirnoboyo Kecamatan pacitan Kabupaten Pacitan - Achmad Ridlowi (LP2M Sekolah Tinggi Agama Islam Nahdlatul Ulama Pacitan, 2017)
Pancasila as a way of life requires Indonesia to transform the values of Pancasila in a real and continuous appreciation and practice of noble values contained in it by every citizen of Indonesia, each state officials as well as any institutions of state and civil society, both in the center or in the region. In social life there is one activity that embodies the implementation of Pancasila values through the activities of the PKK (Family Welfare Empowerment) is an activity initiated by the women in i t has several programs to run 10 (ten) program PKK with the single goal welfare of the family. The grounds are one of the main programs in the PKK, namely The Pancasila, women as objects of research because as the creator of the next generation of national struggle, and in 2015 this village Sirnoboyo used as guided village PKK is as active village and most diligently implement programs PKK.Factors supporting the live in harmony between people, there is no specific provision to follow the activities of the PKK, the evaluation of performance management to produce a nice, family and community support. Inhibiting factors: the chairman of the PKK in the actual practice of not carrying out the duties as chairman of the task, not yet aware of their rights and obli gations.